Study on verification of the feasibility of caption and use of rain water in the municipality of Teófilo Otoni - MG (Research, Society and Development, 2018)
This study has the purpose of verifying the technical viability of rainwater abstraction and use, due to water scarcity, either by population increase, or by waste, or even by polluting activities, rainwater harvesting presents potential to benefit many people, especially for uses considered non-potable, in order to cope with water shortages, making it necessary each day to optimize water use. From the results analyzed it was verified that the capture system is a viable alternative for the reduction of the volume of treated water consumed for the population. The reduction of the cost with the use of rainwater, contributing to the sustainable development of the environment and the improvement of the quality of life, besides the retention of part of the volume of the precipitations contributing to the damping of the surface runoff helping to reduce floods in areas urban, which will be proposed in this work.